Evaluation of stability of underground workings for exploitation of an inclined coal seam by the ubiquitous joint model. (March 2017) - Das, A.J.; Mandal, P.K.; Bhattacharjee, R.; Tiwari, S.; Kushwaha, A.; Roy, L.B.
Abstract: The effect of the inclination of strata and the coal seam on the stability of surrounding rock masses is evaluated by parametric study through numerical modelling. The ubiquitous joint model is used to consider the shearing effect of the bedding planes. The rock load height above the galleries is estimated by calculating the safety factor of immediate roof. It is obtained from the study that the rock load height and stress concentration are comparatively more at the dip side of the working than the rise side. The pillar strength is minimum when the inclination of the coal seam is close to ( π / 4 + ϕ j / 2 ) where ϕ j is the friction angle of the bedding plane. A case study of inclined Jarangdih new seam (10' seam) of Sawang Colliery of Central Coalfields Limited (CCL) in India is presented. The inclination of the coal seam is around 1 in 3. As the coal seam is developed along the apparent dip of 1 in 5, the coal pillars become rhombus shaped with acute angle of 40°. Both numerical modelling and field investigation reveal that the failure zone extends more toward the acute angle of the coal pillar. Thus, heavier support system is installed in the roof at the intersections near acute angles of the coal pillars. Support system is designed based on the rock load height. Extraction methodology including stability analysis has also been presented for depillaring of this inclined coal seam. Highlights: Extraction methodology is designed for an inclined coal seam of gradient around 1 in 3. Failures are found more towards the acute angled corners of rhombus shaped coal pillar. The pillar strength is minimum when the inclination of the coal seam is close to ( π / 4 + ϕ j / 2 ) where ϕ j is friction angle of bedding plane. Roof bolt based support system is designed based on the rock load height. Rock load heights are estimated from the safety factor of immediate roof.